GRP78 Knockdown Enhances Apoptosis via the Down-Regulation of Oxidative Stress and Akt Pathway after Epirubicin Treatment in Colon Cancer DLD-1 Cells - Chang, Yu-Jia; Huang, Yi-Ping; Li, Zih-Ling; Chen, Ching-Hsein (PLOS ONE, 2012)
Introduction The 78-kDa glucose-regulated protein (GRP78) is induced in the cancer microenvironment and can be considered as a novel predictor of responsiveness to chemotherapy in many cancers. In this study, we found that intracellular reactive oxygen species (ROS) and nuclear factor erythroid 2-related factor 2 (Nrf2) nuclear translocation were higher in GRP78 knockdown DLD-1 colon cancer cells compared with scrambled control cells. Methodology/Principal Findings Treatment with epirubicin in GRP78 knockdown DLD-1 cells enhanced apoptosis and was associated with decreased production of intracellular ROS. In addition, apoptosis was increased by the antioxidants propyl gallate (PG) and dithiothreitol (DTT) in epirubicin-treated scrambled control cells. Epirubicin-treated GRP78 knockdown cells resulted in more inactivated Akt pathway members, such as phosphorylated Akt and GSK-3β, as well as downstream targets of β-catenin expression. Knockdown of Nrf2 with small interfering RNA (siRNA) increased apoptosis in epirubicin-treated GRP78 knockdown cells, which suggested that Nrf2 may be a primary defense mechanism in GRP78 knockdown cells. We also demonstrated that epirubicin-treated GRP78 knockdown cells could decrease survival pathway signaling through the redox activation of protein phosphatase 2A (PP2A), which is a serine/threonine phosphatase that negatively regulates the Akt pathway. Conclusions Our results indicate that epirubicin decreased the intracellular ROS in GRP78 knockdown cells, which decreased survival signaling through both the Akt pathway and the activation of PP2A. Together, these mechanisms contributed to the enhanced level of epirubicin-induced apoptosis that was observed in the GRP78 knockdown cells.